Blocking olfactory input alters aggression in male and female California mice (Peromyscus californicus). Issue 3 (27th October 2021) - Bester‐Meredith, Janet K.; Burns, Jennifer N.; Dang, Minh N.; Garcia, Alexandrea M.; Mammarella, Grace E.; Rowe, Melissa E.; Spatacean, Christine F.
Abstract: Olfactory input into the brain can be disrupted by a variety of environmental factors, including exposure to pathogens or environmental contaminants. Olfactory cues are often eliminated in laboratory rats and mice through highly invasive procedures like olfactory bulbectomy, which may also disrupt accessory olfactory pathways and detection of non‐volatile odors. In the present study, we tested whether inducing anosmia through intranasal infusion of zinc gluconate alters aggression in a monogamous, biparental rodent species, the California mouse ( Peromyscus californicus) . This less invasive method of manipulating olfaction selectively targets the olfactory epithelium and reduces the detection of volatile odors. Treatment with zinc gluconate extended the time required for male and female California mice to find hidden pieces of apple and reduced the amount of time spent investigating bedding that was soiled by unfamiliar males. Moreover, inhibition of olfaction with zinc gluconate reduced aggressiveness in both sexes as demonstrated by an increased attack latency in the resident‐intruder test among same‐sex dyads from the same treatment group. These results suggest that volatile olfactory cues are necessary for agonistic responses in both male and female California mice. Therefore, even in species with complex social systems that include territorial aggression and monogamy, volatile olfactory cues modulate agonistic behavior.